Multiple Parenting Relationships in Image Phylogeny: Tracking Down Forgeries and Their Creators Online - Oliveira, Alberto; Rocha, Anderson (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2016: Anais do XXIX Concurso de Teses e Dissertações, 2016)
Due to the large amount of images shared on the web, tracking the spread and evolution of their content have become an increasingly important problem. As an image might be a composition created through the combination of the semantic information existent in two or more source images, establishing a relationship between the sources and the composite is an ever-growing problem of interest. We name as Multiple Parenting Phylogeny the problem of identifying such relationships in a set containing near-duplicate subsets of source and composition images. To tackle this problem, this work presents a three-step solution: (1) separation of near-duplicate groups; (2) classification of the relations between the groups; and (3) identification of the images used to create the original composition. Furthermore, we extend upon this framework by introducing key improvements, such as better identification of when two images share content, and improved ways to compare this content. Evaluation of the proposed method is performed by means of quantitative metrics established for evaluating the accuracy in reconstructing phylogenies and finding multiple parenting relationships in the different datasets. Finally, we also analyze the results qualitatively, with images obtained from the web